Postpartum depression among Pakistani women in Norway: prevalence and risk factors - Bjerke, Soen Eng Y; Vangen, Siri; Nordhagen, Rannveig; Ytterdahl, Tore; Magnus, Per; Stray-Pedersen, Babill (The journal of maternal-fetal & neonatal medicine, 2008)
To assess the prevalence of and risk factors for postpartum depression among Pakistani women in Norway. A total of 207 pregnant Pakistani women living in Norway participated in a questionnaire study. The author interviewed the women face to face during pregnancy and 6 to 12 weeks after delivery. The Edinburgh postnatal depression scale was used to identify the risk cases. Only 7.6% of the immigrant Pakistani women were depressed postpartum. High scores on the life event scale, a history of prior depression, single marital status, a poor relationship to one's partner and an age of 30 years or more were found to be significant risk factors for postpartum depression. The prevalence of postpartum depression among immigrant Pakistani women seems to be low compared with the prevalence reported in immigrant populations elsewhere, it was however only slightly lower than the study of ethnic Norwegians (8.9%). The risk factors were similar to results from international reports; moreover, there were few cultural differences in risk factors between ethnic Norwegian and Pakistani immigrants.